2014
DOI: 10.2319/060613-433.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different orthodontic adhesives and resin removal techniques on enamel color alteration

Abstract: Objective: To investigate the color alterations in enamel following the use of different orthodontic bonding resins and adhesive residue-removal burs. Materials and Methods: Metal brackets were bonded to extracted human premolars (n 5 175) by using an etch-and-rinse adhesive system, a self-etch adhesive system (SEP), or a resin-modified glass ionomer cement (RMGIC). After 24 hours of photoaging, the brackets were removed and the adhesive residue on the tooth surfaces was cleaned with either a tungsten carbide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 29 publications
5
58
1
2
Order By: Relevance
“…It is necessary to completely remove the enamel adhesive to avoid prolonged accumulation of plaque which can cause in the future decalcification and periodontal diseases. By removing the waste on the tooth it will cause physical changes in the enamel ranging from hard surface to microscopic fractures (Boncuk, Çehreli, & Polat‐Özsoy, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to completely remove the enamel adhesive to avoid prolonged accumulation of plaque which can cause in the future decalcification and periodontal diseases. By removing the waste on the tooth it will cause physical changes in the enamel ranging from hard surface to microscopic fractures (Boncuk, Çehreli, & Polat‐Özsoy, ).…”
Section: Discussionmentioning
confidence: 99%
“…Some in vitro studies have concluded that there is no definitive evidence to show the bonding/debonding procedures alone exert significant effect on the colour of both bovine and human tooth enamel . However, other research has indicated that these procedures have a discernible impact on enamel colour . Irrespective of these conflicting conclusions, several reports have emphasized the need for further randomized clinical trials to try to clarify the issue.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 However, other research has indicated that these procedures have a discernible impact on enamel colour. [15][16][17] Irrespective of these conflicting conclusions, several reports have emphasized the need for further randomized clinical trials to try to clarify the issue. In vivo studies have previously revealed colour differences following The results of the present long-term in vivo study indicate that the colour of natural teeth after the first retention year demonstrated significant changes, ranging from 1.4 to 2.1 ΔΕ units.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of nano-particles however, the interfacial properties are altered since these have been found to penetrate the tag (Jogrensen & Shimokobe 1975;Silverstone et al 1975;Irinoda et al 2000). Even colour changes of enamel associated with orthodontic bonding and clean-up procedures were reported (Ye et al 2013;Boncuk et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding alterations include enamel loss induced by enamel etching, inhibition of remineralization by saliva for the area bonded during treatment as well as scratches, and fractures induced on the surface during resin cleaning (Eliades et al 2004). These parameters may affect the enamel colour to a varying extent as suggested by the fact that acid etching and debonding-cleaning procedures have been shown to lead to alteration of the uppermost enamel layer in the order of 10 μm for acid-etching-mediated bonding (Boncuk et al 2014;Zhu et al 2014). The literature indicates that colour and roughness changes after debonding correspond to irreversible structural and colourimetric alterations induced by orthodontic bonding and debonding.…”
Section: Introductionmentioning
confidence: 99%